2012
DOI: 10.1158/1541-7786.mcr-11-0482
|View full text |Cite
|
Sign up to set email alerts
|

Heparin-like Polysaccharides Reduce Osteolytic Bone Destruction and Tumor Growth in a Mouse Model of Breast Cancer Bone Metastasis

Abstract: TGF-b regulates several steps in cancer metastasis, including the establishment of bone metastatic lesions. TGF-b is released from bone during osteoclastic bone resorption and it stimulates breast cancer cells to produce osteolytic factors such as interleukin 11 (IL-11). We conducted a cell-based siRNA screen and identified heparan sulfate 6-Osulfotransferase 2 (HS6ST2) as a critical gene for TGF-b-induced IL-11 production in highly bone metastatic MDA-MB-231(SA) breast cancer cells. HS6ST2 attaches sulfate gr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 35 publications
4
28
0
Order By: Relevance
“…Based on these new findings and those reported previously [16,34,36,37], we propose that IL-11- (A) BMMs were cultured with rM-CSF (10ng/ml) plus RANKL (100ng/ml) as control or M-CSF (10ng/ml) plus IL-11 (5, 10 or 20ng/ml) for 6 days in tissue culture dish. The cultures were then stained for TRAP activity.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Based on these new findings and those reported previously [16,34,36,37], we propose that IL-11- (A) BMMs were cultured with rM-CSF (10ng/ml) plus RANKL (100ng/ml) as control or M-CSF (10ng/ml) plus IL-11 (5, 10 or 20ng/ml) for 6 days in tissue culture dish. The cultures were then stained for TRAP activity.…”
Section: Discussionsupporting
confidence: 70%
“…Since the initial study showing the expression of IL-11 in breast tumor tissues more than 25 years ago [27], numerous investigations have been subsequently undertaken to address the regulation and pathological significance of IL-11 expression in breast cancer and, in particular, in the tumor-induced osteolysis [5,13,[28][29][30][31][32][33][34]. Collectively, these studies have led to two important observations: a) IL-11 is not only expressed in a significant number of breast cancers but also has the potential to serve as a prognostic factor in human breast cancer, and b) IL-11 plays an important role in breast cancer-mediated osteolysis by promoting osteoclastogenesis and bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of H6ST2 in tumor cells impairs cell migration, invasion, tubule formation, and may reverse EMT (10,13,32). Notably, previous reports revealed that the specific inhibition of HS6ST2 by a high molecular weight Escherichia coli K5-derived heparin-like polysaccharide (K5-NSOS), prevented tumor progression in a mouse model of breast cancer metastasis (15). These results indicated that K5-NSOS may be a potential anticancer agent in cancer therapy.…”
Section: Hs6st2 Expression ------------------------------------mentioning
confidence: 82%
“…By way of this mechanism, HSPGs subsequently participate in diverse biological functions including blood clotting, cell recognition, adhesion, proliferation, and differentiation by interactions with diverse cytokines (8,9). Previous studies have revealed that HS6ST2 is associated with the progression of malignant tumors, and is upregulated in various tumor types including thyroid (10,11), colorectal (12), pancreatic (13), ovarian (14), breast cancer (15), and chondrosarcomas (16). However, to the best of our knowledge, the involvement of HS6ST2 in GC has not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The inhibition of HS6ST2 expression has been shown to effectively suppress the proliferation, migration and invasion of pancreatic cancer cells (11). Pollari et al (25) demonstrated that HS6ST2 is an important gene for transforming growth factor-β-induced interleukin-11 production in a mouse model of breast cancer bone metastasis. Recently, HS6ST2 was found to be abundantly expressed in colorectal cancer, and the increased expression of HS6ST2 was found to be associated with poor survival, which is considered a cancer-related marker (26).…”
Section: Discussionmentioning
confidence: 99%